Bovenste rij v.l.n.r.: Rutgers, Kluyver, Mandere, Embden. Onderste rij: Bakker-Van Bosse, Schaper, Dresselhuys, Jong van Beek, Koolen - Deutmann, H.,
Bovenste rij v.l.n.r.: Rutgers, Kluyver, Mandere, Embden. Onderste rij: Bakker-Van Bosse, Schaper, Dresselhuys, Jong van Beek, Koolen.